2016
DOI: 10.1021/jacs.6b04037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Location Sensing Approach by Anisotropic Magnetism of an Endohedral Metallofullerene

Abstract: Location recognition at the molecular scale provides valuable information about the nature of functional molecular materials. This study presents a novel location sensing approach based on an endohedral metallofullerene, Ce@C82, using its anisotropic magnetic properties, which lead to temperature-dependent paramagnetic shifts in (1)H NMR spectra. Five site-isomers of Ce@C82CH2-3,5-C6H3Me2 were synthesized to demonstrate the spatial sensing ability of Ce@C82. Single-crystal structures, absorption spectra, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…Akasaka and co-workers reported paramagnetic 1 HNMR chemical shifts for Ce@C 82 (3,5-dimethylbenzyl). [25] These shifts are explained as pseudocontact shifts because of the felectron spin. In contrast, our data are rationalized by considering both Fermi contact and pseudocontact terms.…”
Section: Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…Akasaka and co-workers reported paramagnetic 1 HNMR chemical shifts for Ce@C 82 (3,5-dimethylbenzyl). [25] These shifts are explained as pseudocontact shifts because of the felectron spin. In contrast, our data are rationalized by considering both Fermi contact and pseudocontact terms.…”
Section: Zuschriftenmentioning
confidence: 99%
“…[24] Therefore,t he signal appears only when NO molecules are trapped in unsymmetrical environments such as zeolites. [25] These shifts are explained as pseudocontact shifts because of the felectron spin. Figure 3.…”
mentioning
confidence: 99%
“…Furthermore, δ fc and δ pc are the functions of 1/ T and 1/ T 2 , respectively (Figure b). Akasaka and co‐workers reported paramagnetic 1 H NMR chemical shifts for Ce@C 82 (3,5‐dimethylbenzyl) . These shifts are explained as pseudocontact shifts because of the f‐electron spin.…”
Section: Figurementioning
confidence: 99%
“…The chemical reactivity of open-shell EMFs has also been explored [8]. Results have revealed that several reactions of open-shell EMFs, particularly those involving radical species, afforded singly bonded derivatives bearing a closed-shell electronic state [53][54][55][56]. Such single-bonding derivatization ability yielding closed-shell products is apparently a general trend for open-shell EMFs, such as trivalent M@C 82 .…”
Section: Single-bonding Derivatization Of Emfsmentioning
confidence: 99%